PENGARUH PERSEPSI SISWA TERKAIT VIDEO PEMBELAJARAN BERBASIS CANVA DAN KETERAMPILAN MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA DI SMK SWASTA BUDI AGUNG MEDAN T.A 2025/2026 - Nofri Yuliara Harahap; Nelly Armayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low learning motivation is one of the problems in the learning process. This study aimed to determine the influence of students’ perceptions of Canva-based learning videos and teachers’ teaching skills on students’ learning motivation. This research employed an ex post facto method with 86 students selected through the total sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression. The results showed that students’ perceptions of Canva-based learning videos had a positive and significant effect on learning motivation (Sig. 0.000 < 0.05), teachers’ teaching skills had a positive and significant effect on learning motivation (Sig. 0.004 < 0.05), and both variables simultaneously had a positive and significant effect on learning motivation (Sig. 0.000 < 0.05) with a contribution of 32.9%. Therefore, positive student perceptions of Canva-based learning videos and good teaching skills can improve students’ learning motivation.